Produksi Ikan Nila (Oreochromis niloticus) Strain Politeknik Negeri Lampung (PoliNILA) dengan Metode Selective Cross Breeding - Faturrohman, Kurnia; Subhan, Rio Yusufi; Fatimah, Nurul; Wijaya, Megawati (Jurnal Akuakultur Sungai dan Danau, 2026)
Tilapia cultivation in Lampung Province still faces many challenges, including the limited availability of tilapia seeds. This is due to the low availability of tilapia broodstock with superior specifications. This poses a challenge for the Lampung State Polytechnic to produce new strains of tilapia broodstock with distinctive advantages, thereby boosting seed production and consumption of tilapia in Lampung Province. One effort that can be made to create new strains of superior tilapia is by using selective cross-breeding between two superior tilapia species, namely the Srikandi tilapia and the Larasati tilapia. Both types of tilapia have their own unique superior characteristics, so it is hoped that this will be able to create new strains of tilapia that combine the advantages of both. The two superior Nile tilapia broodstock will be cross-bred with the composition in Treatment A, namely male Nile tilapia broodstock Srikandi with female Nile tilapia broodstock Larasati and Treatment B, namely female Nile tilapia broodstock Srikandi with male Nile tilapia broodstock Larasati with each treatment having two replications. This research will be conducted for 90 days of maintenance which includes the process of adaptation of broodstock to the environment, the spawning process and the process of maintaining larvae and seeds. The parameters tested include the number of eggs produced (fecundity), egg hatching rate, survival rate of larvae and fish seeds (survival rate), absolute weight and length gain. The observations during the spawning phase showed that treatment B was the best treatment, measured by the number of larvae produced, which was 1,600 larvae, with a survival rate (SR) of 63% during 28 days of maintenance. Data on the growth of tilapia larvae during 28 days of maintenance showed that the control treatment had superior weight growth performance compared to the other two treatments, namely 6 g with a length of 6.4 cm.